2012
DOI: 10.1101/gr.133546.111
|View full text |Cite
|
Sign up to set email alerts
|

Coding exons function as tissue-specific enhancers of nearby genes

Abstract: Enhancers are essential gene regulatory elements whose alteration can lead to morphological differences between species, developmental abnormalities, and human disease. Current strategies to identify enhancers focus primarily on noncoding sequences and tend to exclude protein coding sequences. Here, we analyzed 25 available ChIP-seq data sets that identify enhancers in an unbiased manner (H3K4me1, H3K27ac, and EP300) for peaks that overlap exons. We find that, on average, 7% of all ChIPseq peaks overlap coding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
193
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(210 citation statements)
references
References 50 publications
17
193
0
Order By: Relevance
“…4; Foxg1, Fig. 4B; Twist1, Ruf et al 2011;Birnbaum et al 2012), further supports the notion that regulatory control is exerted by coordinated, and not individual action, of enhancers. It indicates that this integration is orchestrated at the level of the regulatory domain, not at endogenous gene promoters (Marini c et al 2013).…”
Section: Characteristics Of Mammalian Regulatory Domainssupporting
confidence: 52%
“…4; Foxg1, Fig. 4B; Twist1, Ruf et al 2011;Birnbaum et al 2012), further supports the notion that regulatory control is exerted by coordinated, and not individual action, of enhancers. It indicates that this integration is orchestrated at the level of the regulatory domain, not at endogenous gene promoters (Marini c et al 2013).…”
Section: Characteristics Of Mammalian Regulatory Domainssupporting
confidence: 52%
“…These elements are sometimes referred to as eExons. One recent paper (Birnbaum et al, 2012) found that four of seven potential eExons tested functioned to control the expression of nearby genes. Another paper found that enhancers in coding regions target their own gene (Ritter et al, 2012).…”
Section: Discussion Numbers and Types Of Genes Regulated By Fus3mentioning
confidence: 99%
“…Interestingly, two enhancers controlling limb expression are located far centromeric to Dlx5/6, residing within exons 15 and 17 of Dync1i1 [Birnbaum et al, 2012a]. Moreover, one of these was shown to physically associate with the Dlx5/6 promoter regions in mouse limbs.…”
Section: Balanced/unbalanced Chromosome Rearrangementsmentioning
confidence: 99%
“…Moreover, one of these was shown to physically associate with the Dlx5/6 promoter regions in mouse limbs. These exonic enhancers, termed "eExons," have been implicated in human SHFM based on their locations relative to various translocation and inversion breakpoints that are presumed to disrupt their interactions with DLX5/6 [Birnbaum et al, 2012a]. Additional analysis of rearrangements at this locus has led to the delineation of a minimal 1.2 Mb critical region in which other DLX5/6 enhancers might reside [Birnbaum et al, 2012b].…”
Section: Balanced/unbalanced Chromosome Rearrangementsmentioning
confidence: 99%